2017
DOI: 10.2131/jts.42.175
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the early-response genes in chemical-induced renal carcinogenicity for the prediction of chemical carcinogenicity in rats

Abstract: -This study was designed to identify early-response genes of chemical-induced renal carcinogenicity for the prediction of chemical carcinogenicity in rats. We conducted a 28-day repeated-dose test in male Crl:CD (SD) rats with 12 carcinogens and 10 non-carcinogens as the training dataset, and five carcinogens and five non-carcinogens as the validation dataset. Renal gene expression profiles were analyzed by using a microarray. Fifteen candidate genes were selected from the gene expression profiles of the train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
(10 reference statements)
1
5
0
Order By: Relevance
“…But unfortunately, there were not any laboratory experiments evidence conducted in RCC. HAMP is famous for the maintenance of iron homeostasis 57,58 and the regulation of cell growth and cycle 59 . Studies have showed iron metabolism was correlated with inflammation 60 and malignant tumor, such as multiple myeloma, 61 hepatocellular carcinoma, 62 and renal carcinoma 63 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But unfortunately, there were not any laboratory experiments evidence conducted in RCC. HAMP is famous for the maintenance of iron homeostasis 57,58 and the regulation of cell growth and cycle 59 . Studies have showed iron metabolism was correlated with inflammation 60 and malignant tumor, such as multiple myeloma, 61 hepatocellular carcinoma, 62 and renal carcinoma 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, conventional dendritic cells can secrete hepcidin, the product of HAMP, which is noticeable in the inflamed intestine of humans. HAMP has been uncovered to be associated with the prognosis of urothelial carcinoma of the upper urinary tract and RCC 64 and to contribute to the early stage of carcinogenesis 59 . HAMP has a strong correlation with immune and carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 100 chemicals, consisting of 68 chemicals used in prediction systems examining hepatic carcinogenicity and 32 chemicals commonly used in prediction systems examining renal carcinogenicity and detection systems for hepatotoxicity and nephrotoxicity, were selected from among chemicals used in previous studies [11][12][13]. The number of test compounds used in each experiment is shown in Fig.…”
Section: Chemicals Animal Test and Microarray Analysismentioning
confidence: 99%
“…Recently, we reported a renal carcinogenicity prediction system to predict chemical carcinogenicity in rats; a 28-day repeated-dose test was performed using male Crl:CD (SD) rats with 12 carcinogens and 10 non-carcinogens as the training dataset and five carcinogens and five non-carcinogens as the validation dataset [13]. In this prediction system, the prediction accuracies for the training and the validation datasets were calculated to be 100% and 90%, respectively, while 4-hydroxy-m-phenylenediammonium dichloride (AMIDOL), a known non-renal carcinogen, was judged as being positive.…”
Section: Prediction System For Hepatic and Renal Carcinogenicity: Carmentioning
confidence: 99%
See 1 more Smart Citation